Unjustified capital increase in public servants (2016)
The intention of this document is realize a reflection of our literal situation that every time is more habitual regarding public servants that are investigated because their unjustified capital increase, this document guide to realize an analisys of the different strategics of the Nation for intensify the ethics in public servants and finally how this behavior injured the society in general.